2018
DOI: 10.1159/000488024
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Otherwise-Discarded Umbilical Cord Blood as a Source for a Neonate’s Complete Blood Cell Count at Various Time Points

Abstract: Background: Previous studies have reported the use of cord blood for admission laboratory complete blood counts (CBCs). However, no studies have investigated its stability for the first 30 min after delivery. Objectives: We quantified blood cells drawn from the umbilical vein to determine the effect of (1) the time after placental delivery, and (2) the site of blood sampling (umbilical vein on an isolated cord segment vs. umbilical vein on the placental surface). Methods: Timed phlebotomies were drawn at 2, 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In recent decades, implementing RBC Tx-reduction strategies has diminished NICU RBC TX rates [38][39][40][41]. These strategies have included, 1) instituting transfusion guidelines [31,38,39,42], 2) reducing number and volume of blood draws form neonates for laboratory testing [43], 3) delayed umbilical cord clamping [44], 4) umbilical cord milking (if delayed clamping is not possible) [45], 5) drawing initial blood for laboratory tests not from the neonate but from otherwise discarded umbilical cord blood [40,46], 6) selectively administering erythropoietic stimulating agents [47], and 7) assuring iron su ciency [48].…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, implementing RBC Tx-reduction strategies has diminished NICU RBC TX rates [38][39][40][41]. These strategies have included, 1) instituting transfusion guidelines [31,38,39,42], 2) reducing number and volume of blood draws form neonates for laboratory testing [43], 3) delayed umbilical cord clamping [44], 4) umbilical cord milking (if delayed clamping is not possible) [45], 5) drawing initial blood for laboratory tests not from the neonate but from otherwise discarded umbilical cord blood [40,46], 6) selectively administering erythropoietic stimulating agents [47], and 7) assuring iron su ciency [48].…”
Section: Discussionmentioning
confidence: 99%
“…First, we had no data on the timing of umbilical cord sampling. It has been shown that the platelet count was slightly higher if the blood sampling was performed after 10 minutes of placental delivery from the umbilical vein near or on the placental surface or after 30 minutes from an umbilical cord segment [ 47 ]. Second, although our total sample size was large, it was not large enough in certain strata.…”
Section: Discussionmentioning
confidence: 99%
“…In the studies in which umbilical cord and venous blood samples taken simultaneously from newborns, a significant difference was reported between these two samples in terms of CBC results. 6,[11][12][13] In a study conducted with 174 newborns, it was found that leukocyte, neutrophil and lymphocyte counts were significantly higher in umbilical cord blood. 6 However, the authors found the groups similar in terms of mean monocyte, eosinophil and platelet counts.…”
Section: Discussionmentioning
confidence: 99%